ORGANIZATIONAL ACTIVENESS, WORK MOTIVATION, AND SOFT SKILLS ON WORK READINESS OF VOCATIONAL STUDENTS - A'li, Muhammad Hamdi; Zulaihati, Sri; Adha, Maulana Amirul (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2024)
The purpose of this study was to analyze how organizational activity, work motivation, and soft skills affect the work readiness of vocational high school students. This study uses a quantitative method with primary data through the distribution of questionnaires. This study involved a population of 214 students from class XI of SMK Negeri 16 Jakarta. In this study, the proportional random sampling technique was used, using the Issac and Michael table with an error rate of 5% so that the determination of the minimum sampling was 135 respondents. The PLS-SEM data analysis technique was carried out using the SmartPLS version 4 program. The results of the hypothesis test from this study found that the variable of organizational activity affects soft skills, the variable of work motivation affects soft skills, the variable of organizational activity affects work readiness, the variable of work motivation affects work readiness. Then, the soft skill variable does not affect work readiness. Furthermore, the soft skill variable, based on data analysis, does not affect organizational activity and work motivation on work readiness.